2008
DOI: 10.1021/je700552j
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Phase Equilibria of the Reciprocal Quaternary System Containing Sodium, Potassium, Chloride, and Borate Ions at 308.15 K

Abstract: The metastable solubility of the reciprocal quaternary system containing sodium, potassium, chloride, and borate ions and the physicochemical properties corresponding to density, viscosity, pH value, and refractive index at 308.15 K have been studied with the isothermal evaporation method. According to the experimental data, the metastable equilibrium phase diagrams of dry salt and the water phase diagram of the system were plotted. In the dry-salt phase diagram, there are two invariant points, five univariant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 1 publication
0
26
0
Order By: Relevance
“…Empirical equations for predicting density and refractive index of the salt-water system were applied to have correlation with the experimental results [18]: Table 3 for comparison, and the relative deviations between the experimental and calculated values are within 0.73%. Yangtze Scholars and Innovative Research Team in Chinese University (IRT_17R81).…”
Section: Empirical Equations For Density and Refractive Indexmentioning
confidence: 99%
“…Empirical equations for predicting density and refractive index of the salt-water system were applied to have correlation with the experimental results [18]: Table 3 for comparison, and the relative deviations between the experimental and calculated values are within 0.73%. Yangtze Scholars and Innovative Research Team in Chinese University (IRT_17R81).…”
Section: Empirical Equations For Density and Refractive Indexmentioning
confidence: 99%
“…As to the crystalline form of the potassium carbonate–sodium carbonate double salt, Shang Shihua, Harvie, and Zeng Ying et al. found that, in the system including potassium and sodium carbonate, the crystalloid form of the sodium and potassium carbonate double salt is K 2 CO 3 ·Na 2 CO 3 ·12H 2 O at 288 and 298 K. The research studied by our research group found that, , in the system containing K 2 CO 3 and Na 2 CO 3 , the sodium and potassium carbonate double salt exist as K 2 CO 3 ·Na 2 CO 3 ·12H 2 O at 273 K, which is agree with the result of this paper.…”
Section: Results and Discussionmentioning
confidence: 80%
“…The brine of Zabuye Salt Lake in Tibet is famous for its abundance of lithium, potassium, and boron resources, which has significant exploitation value, and it is classified as a carbonate-type alkaline brine; the main composition of this salt lake brine can be attributed to Li + , Na + , K + , Mg 2+ ∥SO 4 2– , Cl – , CO 3 2– , B 4 O 7 2– – H 2 O system. To understand the thermodynamics behavior of the system mentioned above, a series of water–salt systems containing elemental borate have been studied, such as the ternary system K + ∥BO 2 – , OH – – H 2 O at 263 K, K + ∥Cl – (SO 4 2– ), B 4 O 7 2– – H 2 O at 308.15 K, Mg 2+ (K + )∥Cl – , B 4 O 7 2– – H 2 O, Na + ∥B 4 O 7 2– , SO 4 2– – H 2 O, and Li + , Na + ∥B 4 O 7 2– – H 2 O at 273.15 K, and the quaternary system Na + , K + ∥Cl – , borate – H 2 O at 308.15 K, K + ∥Cl – , SO 4 2– , B 4 O 7 2– – H 2 O at 298.15 and 308.15 K, and Li + , Na + ∥SO 4 2– , B 4 O 7 2– – H 2 O at 273.15 K . Commonly, the crystalloid form of the borate is affected by the coexisting ions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate and test the reliability of the experimental method in this work, a comparison of the solubilites in the boundary subsystems [20], shown as equations ( 1) and ( 2), the density and refractive index of the experimental solution were calculated, and the results are listed in Table 3.…”
Section: Resultsmentioning
confidence: 99%